(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
The Pithraj seed has been collected from Gazipur district, Bangladesh. The oil from the seed was extracted by using Soxhlet apparatus using petroleum ether extraction method. Maximum yield of oil was found to be 50 % when the process was carried out for 2.5 hours. The physicochemical properties of the extracted oil were studied. The properties of the oil reveal that the oil corresponds to diesel except acid value and sulphur content. The optimum conditions of the transesterification of the oil was 40% ethanol and 0.45% KOH at 75 0C for 1.5 hours. The optimum yield was more than 95 %. Bangladesh J. Sci. Ind. Res. 50(2), 135-142, 2015